Factors influencing women's decision making in hysterectomy. Issue 3 (March 2018) - Janda, Monika; Armfield, Nigel R; Page, Katie; Kerr, Gayle; Kurz, Suzanne; Jackson, Graeme; Currie, Jason; Weaver, Edward; Yazdani, Anusch; Obermair, Andreas
Highlights: This study explored how Australian women knew about hysterectomy. Most women felt well-informed about their hysterectomy. Women were more aware of the open abdominal approach. Decisions were influenced by surgeon's preference, recovery time, surgical risks. Abstract: Objective: To explore factors influencing how well-informed women felt about hysterectomy, influences on their decision making, and on them receiving a less-invasive alternative to open surgery. Methods: Online questionnaire, conducted in 2015–2016, of women who had received a hysterectomy in Australia, in the preceding two years. Results: Questionnaires were completed by 2319/6000 women (39% response). Most women (n = 2225; 96%) felt well-informed about hysterectomy. Women were more aware of the open abdominal approach (n = 1798; 77%), than of less-invasive vaginal (n = 1552; 67%), laparoscopic (n = 1540; 66%), laparoscopic-assisted (n = 1303; 56%), and robotic approaches (n = 289; 12%). Most women (n = 1435; 62%) reported their gynaecologist was the most influential information source. Women who received information about hysterectomy from a GP (OR = 1.47; 95% CI 1.15-1.90), or from a gynaecologist (OR = 1.3; 95% CI 1.06-1.58), were more likely to feel better informed (p < 0.01). Conclusion: This study is important because it helps clinicians, researchers and health policy makers to understand why many women still receive an open abdominal approach despite many learned societies recommending to avoid it if possible. Practice implications: Additional information, or education about avoiding open abdominal approach where possible may lead to a greater number of women receiving less-invasive types of hysterectomy in the future.